Free Versus Fixed-Ratio Combination of Basal Insulin and GLP-1 Receptor Agonists in Type 2 Diabetes Uncontrolled With GLP-1 Receptor Agonists: A Systematic Review and Indirect Treatment Comparison - Jung, Han Na; Cho, Yun Kyung; Min, Se Hee; Kim, Hwi Seung; Kim, Ye-Jee; Park, Joong-Yeol; Lee, Woo Je; Jung, Chang Hee (Frontiers in Endocrinology, 2022)
Introduction This study evaluates the efficacy and safety of the free up-titration of basal insulin and fixed-ratio combination (FRC) of basal insulin and glucagon-like peptide-1 receptor agonists (GLP-1RAs) in type 2 diabetes mellitus (T2DM) patients inadequately controlled with GLP-1RA. Methods With the use of a systematic literature review of PubMed, Embase, Web of Science, and the Cochrane Library databases through July 2021, randomized controlled trials that compared the free up-titration or FRC with remaining on GLP-1RA in T2DM patients uncontrolled with GLP-1RA were included. A comparison of adding basal insulin to maintaining GLP-1RA and an indirect comparison between the two strategies were conducted on the change in HbA1c, fasting plasma glucose (FPG), target achievement [HbA1c < 7.0%], and the risk of confirmed hypoglycemia. The Cochrane Collaboration’s tool was used to assess the risk of bias. Results Two free up-titration and two FRC trials involving 1,612 participants, all lasting 26 weeks, were included. Both approaches significantly lowered HbA1c levels (weighted mean difference [WMD] −0.75%, 95% CI −0.97 to −0.53) but increased hypoglycemic risk [risk ratio (RR) 7.59, 95% CI 3.35−17.17] compared to the unchanged GLP-1RA. No significant differences were discovered between the two methods regarding the decrease in HbA1c (WMD 0.08%, 95% CI −1.07% to 1.23%), FPG (WMD −2.29 mg/dl, 95% CI −45.07 to 40.49 mg/dl), target achievement (RR 1.03, 95% CI 0.50−2.14), and hypoglycemic risk (RR 0.32, 95% CI 0.03−3.59). Conclusion In patients who failed to reach target HbA1c levels despite the GLP-1RA treatment, both strategies of adding basal insulin, free up-titration and FRC, are comparable options are comparable options.